Mentally Ill and Cute as Hell: Menhera Girls and Portrayals of Self-Injury in Japanese Popular Culture - Seko, Yukari; Kikuchi, Minako (Frontiers in Communication, 2022)
Over the last few decades, self-injury has gained wide visibility in Japanese popular culture from manga (graphic novel), anime (animation), to digital games and fashion. Among the most conspicuous is the emergence of menhera (a portmanteau of “mental health-er”) girls, female characters who exhibit unstable emotionality, obsessive love, and stereotypical self-injurious behaviours such as wrist cutting. Tracing the expansion of this popular cultural slang since 2000, this conceptual paper explores three narrative tropes of menhera – the sad girl, the mad woman, and the cutie. Within these menhera narratives, self-injury functions as a self-sufficient signifier of female vulnerability, monstrosity, and desire for agency. These menhera tropes, each with their unique interpretation of self-injury, have evolved symbiotically with traditional gender norms in Japan, while destabilizing long-standing undesirability of sick/detracted female bodies. The menhera narrative tropes mobilize cultural discourses about female madness and subsequently feed back into the social imaginaries, offering those who self-injure symbolic resources for self-interpretation. We argue that popular cultural narratives of self-injury like menhera may exert as powerful an influence as clinical discourses on the way we interpret, make sense of, and experience self-injury. Being attentive to cultural representations of self-injury thus can help clinicians move toward compassionate clinical practice beyond the medical paradigm.